TRANSFORMATION OF ISLAMIC EDUCATION BASED ON THE QUR'AN AN EXAMINATION OF THE PHILOSOPHICAL MEANING OF IQRA IN SURAH AL-'ALAQ - khoiruddin
Islamic Education has its primary foundation in revelation, with the Qur'an as the source of values that build the whole generation both intellectually, emotionally, spiritually, and morally. Surah Al-'Alaq verses 1-5 become the starting point for the transformation of Islamic Education through the command of